Determinants of Financial Performance in Family-Owned Businesses: Evidence from Indonesian SMEs - Rizky Mahendra; Anisa Putri Lestari (Economics Note, 2026)
Family-owned businesses constitute a substantial proportion of small and medium enterprises (SMEs) in Indonesia and play a significant role in employment creation, economic growth, and regional development. Despite their contribution to the national economy, many family-owned SMEs continue to experience challenges in achieving sustainable financial performance due to limitations in managerial capability, financial knowledge, and access to external financing. While previous studies have primarily examined the influence of family ownership on firm performance in publicly listed companies, limited empirical evidence has explored the combined effects of family ownership, financial literacy, and access to finance on the financial performance of Indonesian family-owned SMEs. This study aims to analyze the determinants of financial performance in family-owned SMEs by examining the effects of family ownership, financial literacy, and access to finance. A quantitative explanatory research design was employed using a survey of 185 owners and managers of family-owned SMEs operating in various business sectors across Indonesia. Data were collected through structured questionnaires measured using a five-point Likert scale and analyzed using multiple linear regression with IBM SPSS Statistics 27. The findings indicate that family ownership, financial literacy, and access to finance each have a positive and significant effect on financial performance. Among the examined variables, financial literacy demonstrates the strongest influence, followed by access to finance and family ownership. The results suggest that effective family involvement supported by sound financial knowledge and adequate financing opportunities enables SMEs to improve profitability, operational efficiency, and business growth. The study contributes to the literature on family business management by providing empirical evidence from Indonesian SMEs and offers practical implications for entrepreneurs, financial institutions, and policymakers in strengthening the competitiveness and financial sustainability of family-owned enterprises.